Penerapan Social Network Analysis dalam Penentuan Centrality Studi Kasus Social Network Twitter - Budi Susanto; Herlina Lina; Antonius Rachmat Chrismanto (Jurnal Informatika, 2012)
The twitter provides a kind of relation between users in specific form. When someone follow others, it doesn’t mean that she/he know well about them. We have defined a friend relationship between users in twitter as connection following and follower between two users. Based on this definition we develop a system to get friends and also friends of friends relation from a specific user. We use twitter API to get following and follower list and then construct a graph that represent a social network between those users. From this graph, we analyse the centrality using SNA (Social Network Analysis) method, i.e. closeness and betweeness. We propose to use these methods in order to find out who is the most influence user in the his/her social network to spread out the tweet or information. With this system, user can know about their social network based on their friend list on twitter.   Kata Kunci : Social Network Analysis, Betweenness Centrality, Closeness Centrality